2017
DOI: 10.1002/jcc.24793
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical calculations of tryptophan → heme electron and excitation energy transfer rates in myoglobin

Abstract: The development of optical multidimensional spectroscopic techniques has opened up new possibilities for the study of biological processes. Recently, ultrafast two‐dimensional ultraviolet spectroscopy experiments have determined the rates of tryptophan → heme electron transfer and excitation energy transfer for the two tryptophan residues in myoglobin (Consani et al., Science, 2013, 339, 1586). Here, we show that accurate prediction of these rates can be achieved using Marcus theory in conjunction with time‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 68 publications
(98 reference statements)
0
15
0
Order By: Relevance
“…18, it was suggested that the pathway for the electron transfer proceeds via leucine 69 (Leu69) and valine 68 (Val68) residues, which are in van der Waals contact with each other, while Leu69 is in van der Waals contact with Trp14. This was recently supported by a theoretical modelling of the Trp-heme electron transfer 205 . While the above results of a Trp-mediated electron transfer competing with FRET are especially important for the fundamental understanding of electron transfer in biological systems, from a practical point of view, they underscore a limitation of Trp as the “spectroscopic ruler” in FRET studies of protein dynamics 206 .…”
Section: Intermolecular Charge Transfermentioning
confidence: 74%
“…18, it was suggested that the pathway for the electron transfer proceeds via leucine 69 (Leu69) and valine 68 (Val68) residues, which are in van der Waals contact with each other, while Leu69 is in van der Waals contact with Trp14. This was recently supported by a theoretical modelling of the Trp-heme electron transfer 205 . While the above results of a Trp-mediated electron transfer competing with FRET are especially important for the fundamental understanding of electron transfer in biological systems, from a practical point of view, they underscore a limitation of Trp as the “spectroscopic ruler” in FRET studies of protein dynamics 206 .…”
Section: Intermolecular Charge Transfermentioning
confidence: 74%
“…In a recent theoretical modelling of the Trp-heme electron transfer Suess et al confirmed our hypothesis. [46] The above results of a Trp-mediated electron transfer competing with FRET are especially important for the fundamental understanding of electron transfer in biological systems, but also show a limitation of Trp as a spectroscopic ruler in FRET studies of protein dynamics. Indeed, evidence that FRET is taking place requires not only the decay of the donor fluorescence, but also the detection of the acceptor luminescence, a criterion that is often overlooked in studies of protein dynamics.…”
Section: Time-resolved Fluorescencementioning
confidence: 95%
“…Fluorescence up-conversion is ideal in this respect and as an example we show here the case of the cascade of electronic states in an iridium complex, Ir(ppy) 3 , upon 266 nm excitation of its high-lying ligand-centred (LC) electronic state. [47] The luminescence of Ir(ppy) 3 in DMSO upon 266 nm excitation of its LC state is shown in Fig. 7 as a function of wavelength and time delay.…”
Section: Coordination Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The geometries and energies of the excited states were calculated using the Time Dependent Density Functional Theory (TDDFT), using IQMol (version 2.11.1) software to perform computational calculations 52,53 . The B3LYP functional was used to predict the structural properties as well as the excitations involving charge transfer 54 .…”
Section: Dinamicsmentioning
confidence: 99%